An Incursion Into the Reality of Money Transfer Programs in Brazil and Argentina: 2016-2021 - Da Silva E Silva, Maria Ozanira (2021)
The article referenced in results of several empirical, documental and bibliographical research studies about money transfer programs developed under the coordination and with the participation of the authors, discusses the reality of these programs under implementation in Brazil and Argentina, situating them in the 2016-2021 period. It begins with the socioeconomic and political context of both countries, highlighting the prevalence of ultraliberalism with negative repercussions on the labor market and on poverty, a situation which is rendered worse by the Covid-19 pandemic. It also discusses the debate, reality and implementation of more significant money transfer programs in Brazil and Argentina, to conclude by highlighting the significant contribution of the latter in forming social protection systems in Latin America, focusing on Brazil and Argentina.